The Development Of An Information Sharing Linkage Scale For Service Sector - Ya'kob, SA; Jamal Abdul Nassir Shaari; Abu Bakar, NA (Univ Malaysia Sarawak, Fac Economics & Business, 2024)
This study was done to evaluate the validity of an information sharing linkage scale which will be used for small and medium enterprises (SMEs) in service sector. Content validity is evaluated by six experts in the field and quantified as content validity index (CVI). Content validity assessment is inclusive of four rating criteria which are relevance, clarity, simplicity and ambiguity. All items that fulfil the criteria of content validity index which is at least 0.75 are usable for research instrument. The final version of linkages was improvised in 35 items with 3 factors for information sharing linkage i.e. customer linkage, supplier linkage, and internal linkage; 2 factors for firm performance i.e. operational performance and financial performance.